Pengaruh Pemanasan Basah Dengan Autoklaf Terhadap Aktifitas Senyawa Toxalbumin Pada Biji Kemiri (Aleurites moluccana (L.) Willd) - Mamang, Mamang; Bilang, Mariyati; Salengke, Salengke (Indonesian Journal of Chemical Research, 2018)
In addition to nutritional and non-nutritional content, candlenut also contains toxalbumin, toxic compound that can inhibit protein synthesis. This study aims to inhibit toxalbumin activity in candlenut through moist heating treatment, using hemagglutination method. Defatted candlenut powder was being treated under moist heating using autoclave at the temperature of 121oC for 5,10, 15 and 20 minutes followed by oven heating at the temperature of 70oC for 7 hours and control, continued by dry heating using oven at the temperature of 70oC for 7 hours and extraction using 0.15 M NaCl at room temperature then precipitated using ammonium suplhate (60%) at room temperature for 4 hours. Supernatant was dialyzed with water and 0.15 M NaCl for 1 night each then being freeze dried. 1 g of obtained protein fraction was purified in Sephadex G-75 (10 cm x 1.0 cm) column. Resulted extract was re-dried using freeze dryer for hemagglutination test towards A, B, AB and O blood types. The result shows that toxalbumin acitivities were inhibited by moist heating in autoclave at the temperature of 121oC for 10 minutes followed by drying in oven 70oC for 7 hours.